2011
DOI: 10.29333/ejgm/82753
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Using 112 Emergency Ambulance Services in Turkey and the Province of Konya

Abstract: Aim:The purpose of this study is to evaluate and compare the use of 112 emergency ambulance services in Konya and Turkey within the years 2007, 2008, and 2009 Method: A retrospective descriptive study has been referred. The study variables are the number of ambulances, the reason for the emergency call, number of cases, preliminary diagnoses of the ambulance crew, and the results of crew intervention. Result:In the case of analysing the reasons of ambulance calls carried out in these three years; it is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…conducted a study in Turkey in this regard and reported that trauma and cardiovascular disease were the main reasons for emergency service phone calls. [ 30 ] A Norwegian annual report (2001) showed trauma (41%) and cardiovascular diseases (27%) were the main causes of EMS missions. [ 31 ] According to a report by the Turkish Ministry of Health (2006), trauma (25.7%) and heart diseases (19.5%) were the two major reasons for dispatching ambulances.…”
Section: Discussionmentioning
confidence: 99%
“…conducted a study in Turkey in this regard and reported that trauma and cardiovascular disease were the main reasons for emergency service phone calls. [ 30 ] A Norwegian annual report (2001) showed trauma (41%) and cardiovascular diseases (27%) were the main causes of EMS missions. [ 31 ] According to a report by the Turkish Ministry of Health (2006), trauma (25.7%) and heart diseases (19.5%) were the two major reasons for dispatching ambulances.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, an analysis of calls to the Kayseri 112 Emergency services shows that only 37.50% of calls were classified as genuine and necessary 18 . Another finding was that trauma, cardiovascular diseases (medical conditions) and traffic accidents were the most frequent reasons for calls 17, 18, 19, 20, 21. Finally, very low levels of awareness that the ambulance emergency call number was also used for the Turkish coast guard service, and males, and the young and educated were found to make greater use of the emergency call number compared to other demographic groups 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the usage of EMS and ambulances in Turkey has been examined on the basis of age, gender, reason for calls, the preclinical diagnosis of crews, and the intervention outcomes of ambulance crew. 17 , 18 , 19 , 20 , 21 The major findings of these studies can be summarized as follows: First, the rate of ambulance use in Turkey, even in İzmir, one of the most populous cities, is lower compared to developed countries. 17 Secondly, an analysis of calls to the Kayseri 112 Emergency services shows that only 37.50% of calls were classified as genuine and necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will assume that 10% of these will be high power tractors that will need fuel cells. The number of ambulances per capita was about 1 per thirty thousand people in Turkey [40] and 1 per 4350 people in Australia ( [41] Table 9A.39), figures that we will consider to be representative of an average developing country and a mean developed country, respectively. We will assume that the number of police cars is the same as the number of ambulances.…”
Section: Transportationmentioning
confidence: 99%